Rotavirus-Induced Lipid Droplet Biogenesis Is Critical for Virus Replication - Criglar, Jeanette M.; Estes, Mary K.; Crawford, Sue E. (Frontiers in Physiology, 2022)
A variety of pathogens, including viruses, bacteria and parasites, target cellular lipid droplets for their replication. Rotaviruses (RVs) infect the villous epithelium of the small intestine and are a major cause of acute gastroenteritis in infants and young children worldwide. RVs induce and require lipid droplets for the formation of viroplasms, sites of virus genome replication and nascent particle assembly. Inhibitors of fatty acid synthesis or chemicals that interfere with lipid droplet homeostasis decrease the number and size of viroplasms and the yield of infectious virus. We used a genetically engineered RV, delayed in viroplasm assembly, to show an early interaction of RV nonstructural protein NSP2 and the lipid droplet-associated protein phospho-PLIN1. The interaction between NSP2 and phospho-PLIN1 suggests that we have identified part of the mechanism of RV-induced lipid droplet formation. These studies demonstrate that RV is an excellent model to dissect the cellular process of lipid droplet formation and to determine how RV induces and usurps lipid droplet biogenesis to form viroplasm/lipid droplets.